DETECTION AND ANTIBIOTIC SUSCEPTIBILITY TEST OF ENTEROCOCCUS SPP. FROM DIFFERENT CLINICAL SAMPLES IN DUHOK CITY/ IRAQ - JALAL, RAND BAHDEEN; ABDULLAH, BLAND HUSAMULDEEN (Journal of Duhok University, 2023)
Enterococci a variety of species and formerly believed to be of no medical importance; recently they emerged as life threatening multidrug-resistant (MDR) nosocomial pathogens. Enterococcus faecalis and Enterococcus faecium make up the majority of clinical isolates. Furthermore, these bacteria are naturally resistant to most commonly used antibiotics. The study assesses the prevalence of Enterococcus spp. in different clinical samples; pinpoints the prevalence of species causing infection in this area and finally analyzes the patterns of drug resistance of these isolates. A total of 560 samples were collected and plated on blood and chocolate agar. Species identification and antibiotic susceptibility testing were performed using automated VITEK 2 system. Four species of Enterococci were isolated: E. faecalis (74%), E. faecium (18%) and only (4%) of each E. gallinarum and E. avium. E. faecalis had a (100%) rate of resistance to Gentamycin. E. faecium, a rate of (100%) resistance to Benzylpenicillin. E. gallinarum showed complete resistance to a variety of antibiotics. E. avium showed complete resistance to Ampicillin and Tetracycline. Enterococci represent an infection control challenge in the region, a careful usage of antibiotics and implementation of infection control practices is believed to reduce the risk of infection